EFFECT OF HYDROCOOLING ON POSTHARVEST QUALITY AND SHELF LIFE OF ARUGULA - da Costa, Isaías Alves; de Araújo, Nicolas Oliveira; de Souza, Filipe Bittencourt Machado; Freire, Ana Izabella; da Silva, Leonardo França; Garcia, Fernando Henrique Silva; De Souza, Giovanna Maciel; Fonseca, Guilherme Godoy; da Silva Júnior, João José (Seven Editora, 2026)
Arugula is appreciated as a food. Hydrocooling promotes the reduction of respiration, transpiration and promotion, promoting quality and extending shelf life. The objective of this work was to analyze the influence of hydrocooling and refrigerated storage on post-harvest arugula conservation. As variable variables were: visual and shelf fresh, loss of leaf mass analysis and byl content. The experiment was fully developed in hydrores design, wet control, experimented in fully developed design (control, wet control, experimented in design) with seven procedures. Data were selected using the normality and homology of variances test, analysis of variance (ANOVA) and mean test (Tukey 5%) in software R version 3.6.3. Visual and shelf analysis on the 8th day of storage showed that arugula was not suitable for commercialization in treatments. The weight loss of fresh leaves was 39% without control, 41% without wet control and 40% without hydrocooling. The chlorophyll content differed only on day 0 of storage. The shelf life hidrolagors do not extend the shelf life 12 ºC after arugula or arugula.